Physical exercises for preventing injuries among adult male football players: A systematic review - Pérez-Gómez, J.; Adsuar, J. C.; Alcaraz, P. E.; Carlos-Vivas, J. (Journal of Sport and Health Science, 2022)
Background Football is the most practised sport in the world and is associated with the risk of injuries in the players. Some studies have been published that identify injury prevention programs, but there is no review of the full body of evidence on injury prevention programs for use by football coaches. The aim of this article was to carry out a systematic review of published studies on injury prevention programs for adult male footballers, identify points of common understanding and establish recommendations that should be considered in the design of injury prevention strategies.